Peran Tetua Adat di Desa Wisata Rancakalong dalam Melestarikan Warisan Budaya Takbenda Upacara Adat Ngalaksa - Silkvi Kheir Rahma; Ute Lies Siti Khadijah; Rully Khairul Anwar (Society, 2025)
The Ngalaksa traditional ceremony is a significant cultural practice in Rancakalong, Sumedang, West Java, serving as a vital medium for preserving intangible cultural heritage. While prior studies have explored the broader significance of such ceremonies, limited research has examined the specific roles and challenges faced by traditional elders in safeguarding these traditions amid modernization and globalization. This study addresses this gap by analyzing the multifaceted roles of traditional elders in the Rancakalong Tourism Village in preserving the intangible cultural heritage embodied within the Ngalaksa traditional ceremony. Employing a qualitative approach with a case study method, data were collected through observations, in-depth interviews, and documentation. The findings highlight the critical roles of traditional elders as ceremonial leaders, guardians of cultural values, and, most importantly, key knowledge transmitters who bridge the past and present, ensuring the authentic transmission of traditions to younger generations. This study reveals that the elders’ efforts extend beyond ceremonial continuity; they also serve as a form of resistance against the homogenizing forces of modernization, playing a crucial role in maintaining cultural identity and local wisdom. The study concludes that supporting and empowering traditional elders is essential not only for preserving the Ngalaksa traditional ceremony but also for ensuring the continuity of cultural heritage amid evolving socio-cultural landscapes. These findings have implications for policy development aimed at strengthening community-based cultural preservation initiatives and promoting sustainable tourism practices that respect and value indigenous knowledge systems.